Effects of Climate Change on Nine Rainfed Zea mays Races in Chiapas, Mexico - Vázquez Moreno, Alejandro; Rioja Paradela, Tamara Mila; Carrillo Reyes, Arturo; Orantes García, Carolina; Espinoza Medinilla, Eduardo (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2026)
Maize cultivation (Zea mays) is essential for Mexico from a nutritional, cultural and economic perspective. Scientific literature ignores the impact of anthropogenic causes of climate change on rainfed cultivation of Z. mays in Chiapas, Mexico, one of the poorest states in the country. Therefore, we modeled the feasibility of rainfed cultivation for nine races of rainfed maize for the years 2060 and 2100. The MaxEnt 4.4.4 algorithm modeled maize cultivation under two scenarios (4.5 and 8.5) for 2060 and 2100. Model inputs were 12 bioclimatic variables, 3 climatic variables, and 1 elevation variable. All layers were obtained from the WorldClim 2.1 project. By 2060, the suitable area for rainfed cultivation of the nine Z. mays races would drastically decrease under both modeled scenarios. By 2100, this area will decrease for seven races, and disappear for the Olotillo and Olotón races. To the best of our knowledge, this is the first study providing fundamental information on how climate change will negatively impact the nine Z. mays races in Chiapas, Mexico. This enables the development of sustainable management protocols or conservation strategies. Highlights: The MaxEnt algorithm proved very useful in modeling the effect of climate change on Zea mays. By the year 2060, the viable rainfed cultivation area of the nine mays races will drastically decrease under climate change scenarios 4.5 and 8.5 in Chiapas, México. By the year 2100, the viable rainfed cultivation area of seven mays races will drastically decrease under climate change scenarios 4.5 and 8.5, while Olotillo and Olotón maize races will completely disappear in Chiapas, México. “Maximum temperature of the warmest month” (Bio 5) was the variable with more contribution in 2060 (74% and 92.6%, for 4.5 and 8.5 scenarios, respectively) and in 2100 (59.3% and 89.1%, for 4.5 and 8.5 scenarios, respectively).